Motion analysis of arm movement during badminton smash - Salim, M. S.; Lim, H. N.; Salim, M. S. M.; Baharuddin, M. Y. (Proceedings of 2010 IEEE EMBS Conference on Biomedical Engineering & Sciences (IECBES 2010) Kuala Lumpur, Malaysia, 30th November -2nd December 2010., 2011)
In badminton, it demands excellent physical fitness and good motor coordination for the development of sophisticated racquet movement. This project aims at identifying the difference of forehand overhead smash performed by male and female players. The parameters to study were focused on upper arm, forearm and wrist segments. Qualisys Track Manager (QTM) software and five Oqus camera system were used to record and analyze the performance of e subjects. Eight male and eight female participants served as the subjects. Reflective markers were attached at the key locations on the subject's arm to observe the arm movement during the execution of smash. The subject was directed to stand on the position of the smashing area within the measurement volume and his/her partner who was assigned to serve was directed to stand in the serving area. A sequence of badminton smash movements, from the position of holding racket to smashing motion was captured by the camera. The results obtained indicated that the male subject has higher racquet grip velocity than the female subject. The movement of shoulder abduction and elbow extension were anticipated to be the key contributor for the male players to perform a rapid smash. The female subjects showed a synchronized and significant range of motion especially in the wrist rotation.